An Efficient Class of Estimators in Stratified Random Sampling with an Application to Real Data - Shashi Bhushan; Anoop Kumar; Showkat Ahmad Lone; Sadia Anwar; Nevine M. Gunaime (Axioms, 2023)
This research article addresses an efficient separate and combined class of estimators for the population mean estimation based on stratified random sampling (StRS). The first order approximated expressions of bias and mean square error of the proposed separate and combined class of estimators are obtained. A comparative study is conducted to determine the efficiency conditions in which the suggested class of estimators outperforms the contemporary estimators. These efficiency conditions are examined through an extensive simulation study by employing a hypothetically drawn symmetrical and asymmetrical populations. The simulation results have shown that the suggested class of estimators is more effective than the other available estimators. In addition, an application of the proposed methods is also presented by examining a real data set.